Sexual minority status and child maltreatment: How do health outcomes among sexual minority young adults differ due to child maltreatment exposure?. (October 2019) - Paul, June C.; Monahan, Emma Kahle
Abstract: Background: Although prior studies indicate heightened health and well-being concerns for sexual minority (SM) youth, as well as for youth exposed to child maltreatment in the general population, it is unclear whether there are differences in these outcomes among SM youth that have and have not experienced maltreatment. Objective: Our aim was to investigate the unique associations between child maltreatment and emerging health outcomes beyond the impact of SM status. Data was drawn from a nationally representative sample of 648 SM youth in the U.S. in grades 7–12 during the 1994–1995 school year. Methods: Using data from the National Longitudinal Study of Adolescent to Adult Health, descriptive statistics and ordinary least squares regression models were used to investigate differences in SM young adult outcomes by experiences of child maltreatment. Results: Maltreatment among SM individuals showed strong associations with poor adult mental health outcomes (e.g. depression, anxiety, isolation, and suicidal ideation) and fairly strong negative associations with general health outcomes (e.g., heart and lung problems) when compared to their non-maltreated peers. Associations with maltreatment and behavioral health and socioeconomic outcomes were not as strong for this population, which suggests the effects of maltreatment for SM youth are most salient in regards to mental and physical health. Conclusions: Findings provide insight into what areas of health and well-being should be focused on when working with SM youth that have been maltreated, and offer evidence to encourage further exploration of the outcomes of SM maltreated individuals in young adulthood.